Spatial dynamics of dissolved organic matter among different segments of a large-scale reservoir in the water-level declining period - Wang, Kai; Xiao, Shangbin; Liu, Jia; Li, Penghui; He, Chen; Shi, Quan; He, Ding (Frontiers in Environmental Science, 2022)
Large-scale reservoirs exhibit complex hydrological conditions and exert a significant alteration on river flowing. Although dissolved organic matter (DOM) is noted to involve in biogeochemical processes, the variation mechanism of DOM chemistry across a large-scale reservoir is not well assessed. Here we investigated four tributaries across different segments (e.g., the front and non-front areas) of the world’s largest Three Gorges Reservoir (TGR). Optical techniques and ultrahigh-resolution mass spectrometry were used to comprehensively explore the variation of DOM chemistry across TGR in the water-level declining period and biological incubation experiments were conducted to trace its biogeochemical influences. We found that the variation of DOM composition and property between tributary and river mouth sites showed different patterns between front and non-front areas of TGR. In particular, there was more terrestrial derived and biologically recalcitrant DOM in the river mouth than tributaries in the front area, while the opposite variation was observed in the non-front area. Integrated with hydrological information, the results demonstrated that the density current exerts a significant influence on DOM dynamics. Furthermore, the biological incubation experiments suggest that this variation of DOM property among tributaries would involve in the spatial dynamics of carbon dioxide (CO2) emission in TGR that more CO2 emission in the tributary of the front area than of non-front area during the water-level declining period.